Viscosity measuring cell using ultrasonic wave mode conversion - Buiochi, F.; Franco, E. E.; Higuti, R. T.; Adamowski, J. C. (Taylor & Francis Ltd, 2006)
This work presents a cell to measure dynamic viscosity of liquids using ultrasonic wave mode conversion from longitudinal to shear wave. The strategy used to obtain the viscosity is based on the measurement of the complex reflection coefficient of shear waves at a solid-liquid interface. Viscosity measurements of automotive oils (SAE90 and SAE140) were obtained in the frequency range from 1 to 10 MHz. These results are compared with the Maxwell model with two relaxation times, showing the dependency of viscosity with frequency. Several parameters affecting viscosity measurements, including the solid material properties, liquid viscosity, and operating frequency are discussed.
Keywords: ultrasound; viscosity; measurement cell; mode conversion